2010
DOI: 10.1186/1471-2180-10-226
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulation of a chronic bacteria infection and consequences for pathogen transmission

Abstract: BackgroundThe role of host immunity has been recognized as not only playing a fundamental role in the interaction between the host and pathogen but also in influencing host infectiousness and the ability to shed pathogens. Despite the interest in this area of study, and the development of theoretical work on the immuno-epidemiology of infections, little is known about the immunological processes that influence pathogen shedding patterns.ResultsWe used the respiratory bacterium Bordetella bronchiseptica and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 39 publications
9
55
0
Order By: Relevance
“…Between-rabbit variation in protective anti- B. bronchiseptica immunity – and hence resistance to infection – is likely to at least partly explain differences in host susceptibility to infection. Indeed, recent work has shown that the protective immune response against B. bronchiseptica varies between individual rabbits, with robust serum IgG detected in some hosts for up to 5 months post infection, which correlated with clearance from the respiratory tract [28]. Given the persistent nature of B. bronchiseptica infections in rabbits – infections of 5 months were routinely recorded [28] – and other mammals [23], the decline in prevalence we observe is unlikely to be driven by bacteria clearance and recovery.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Between-rabbit variation in protective anti- B. bronchiseptica immunity – and hence resistance to infection – is likely to at least partly explain differences in host susceptibility to infection. Indeed, recent work has shown that the protective immune response against B. bronchiseptica varies between individual rabbits, with robust serum IgG detected in some hosts for up to 5 months post infection, which correlated with clearance from the respiratory tract [28]. Given the persistent nature of B. bronchiseptica infections in rabbits – infections of 5 months were routinely recorded [28] – and other mammals [23], the decline in prevalence we observe is unlikely to be driven by bacteria clearance and recovery.…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, recent work has shown that the protective immune response against B. bronchiseptica varies between individual rabbits, with robust serum IgG detected in some hosts for up to 5 months post infection, which correlated with clearance from the respiratory tract [28]. Given the persistent nature of B. bronchiseptica infections in rabbits – infections of 5 months were routinely recorded [28] – and other mammals [23], the decline in prevalence we observe is unlikely to be driven by bacteria clearance and recovery. Rather, some level of enhanced immune protection in older age-classes may be responsible for conferring some level of anti-bordetella resistance.…”
Section: Discussionsupporting
confidence: 52%
“…RNA isolation, reverse transcription and qRT-PCR quantification were performed following protocols we have developed [28], [31].…”
Section: Methodsmentioning
confidence: 99%
“…The low frequency of transmission of B. bronchiseptica between wild-type mice suggests that mice either shed insufficiently or that they are highly resistant to colonization. In rabbits, the intensity and duration of shedding varied with inter-individual differences in bacterial load, serum antibody titers and cytokine responses, demonstrating that the nature and strength of immune responses affect the transmissibility of B. bronchiseptica [18]. Since immunity may restrict the transmission of B. bronchiseptica , we employed the tools available for mouse immunology to investigate how host immune components affect transmission.…”
Section: Introductionmentioning
confidence: 99%